Going global: Indian adolescents' eating patterns. Issue 15 (12th May 2016) - Shaikh, Nida I; Patil, Shailaja S; Halli, Shiva; Ramakrishnan, Usha; Cunningham, Solveig A
Abstract: Objective: To describe adolescents' eating patterns of traditional, global/non-local and mixed foods, and the factors that may influence food consumption, access and preferences, in a globalizing city. Design: A representative sample of school-going adolescents completed a cross-sectional survey including an FFQ designed to identify traditional and global foods. Student's t test and ordinal logistic regression were used to examine weekly food intake, including differences between boys and girls and between adolescents attending private and public schools. Setting: Vijayapura city, Karnataka State, India. Subjects: Adolescents ( n 399) aged 13–16 years. Results: Compared with dietary guidelines, adolescents consumed fruit, green leafy vegetables, non-green leafy vegetables and dairy less frequently than recommended and consumed energy-dense foods more frequently than recommended. Traditional but expensive foods (fruits, dairy, homemade sweets and added fat) were more frequently consumed by private-school students, generally from wealthier, more connected families, than by public-school students; the latter more frequently consumed both traditional (tea, coffee, eggs) and mixed foods (snack and street foods; P ≤0·05). Girls reported more frequent consumption of global/non-local packaged and ready-to-eat foods, non-green leafy vegetables and added fat than boys ( P ≤0·05). Boys reported more frequent consumption of eggs and street foods than girls ( P ≤0·05). Conclusions: Adolescents' eating patterns in a globalizing city reflect a combination of global/non-local and traditional foods, access and preferences. As global foods continue to appear in low- and middle-income countries, understanding dietary patterns and preferences can inform efforts to promote diversity and healthfulness of foods.